MIDI Controller Design Using Arduino Leonardo as a Digital Audio Workstation (DAW) Management Tool - Santiko, Irfan; Darso, Darso (ACSIT, 2024)
It is very possible for a musician who works in the modern technology era to be familiar with digital sounds or tones. They even use technology in music in the modern era. Currently, there are many models of digital music devices, both physical and non-physical. One of them is a digital effect for bass and guitar. The size of the device ranges from large to simple. The obstacle faced is that musicians, especially those who are still new to utilizing technology, often have difficulty controlling it. This is due to the simple design of the device, which makes it more difficult to use on stage because of the many preset tones and controls available. Because digital effects require large storage capacity, their function is similar to the processor in the CPU. Technology devices such as the Digital Audio Workstation (DAW) feature, allow users to produce their own music without having to rent a recording studio. On this occasion, this article will discuss the design of a MIDI manager model as a tool in carrying out the audio processing process. In the design we use Arduino Leonardo technology with an ATmel Mega 32u4 processor as the control engine. The result is a device that can control features in DAW which makes it easier for musicians to manage audio both during the recording process and on stage.